The Effect of Concrete-Pictorial-Abstract (CPA) Approach on The Decrease of Mathematical Anxiety in Primary School - Putri, Hafiziani Eka; Muqodas, Idat; Wahyudy, Mukhamad Ady; Nuraeni, Fitri (International Conference on Elementary Education, 2020)
Mathematics is still regarded as a difficult subject that promotes students’ anxiety. The aim of this study is to investigate the effect of Concrete-Pictorial-Abstract (CPA) approach on the decrease of students’ mathematical anxiety in primary school. This study use Research and Development (RnD) model which includes descriptive, experimental and evaluative methods. Experimental method was used to identify the effect or the efficacy of CPA approach implementation on the decrease of students’ mathematical anxiety. The subjects of this study were 131 fifth grade students in two different primary schools in Subang and Karawang, West Java. The lesson was implemented by assigning students into two groups: (1) students who experienced learning with Concrete-Pictorial-Abstract (CPA) as experimental group and (2) students who experienced learning with convensional method as control group. Inferential data analysis suggests the significant effect of Concrete-pictorialAbstract (CPA) implementation on the decrease of students’ mathematical anxiety in primary school. This evidence is supported by the calculation of determinant test which imply high percentage of Concrete-Pictorial-Abstract (CPA) effecton the decrease of students’ mathematical anxiety in primary school. Therefore, instruction with CPA can be used as an alternative solution to reduce mathematical anxiety of students in primary school